2005
DOI: 10.1242/jeb.01409
|View full text |Cite
|
Sign up to set email alerts
|

Sodium and anion transport across the avian uterine (shell gland)epithelium

Abstract: transport were coupled under basal and cAMP stimulated conditions and basal anion transport decreased with age and during molting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 28 publications
0
17
1
Order By: Relevance
“…The cAMP-induced decrease in I sc is in contrast with the results obtained by Vetter and O'Grady (2005) in stripped epithelia. Those authors measured a significant higher I sc in the presence of Clafter 8-CPT-cAMP administration.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…The cAMP-induced decrease in I sc is in contrast with the results obtained by Vetter and O'Grady (2005) in stripped epithelia. Those authors measured a significant higher I sc in the presence of Clafter 8-CPT-cAMP administration.…”
Section: Discussioncontrasting
confidence: 99%
“…Our results indicate an HCO 3 secretion confirmed by data obtained with the membrane-permeable cAMP analogue, 8-CPT-cAMP. The latter drug stimulated an HCO 3 secretion that was inhibited by block of carboanhydrases (Vetter and O'Grady, 2005). The pathway for this electrogenic secretion could occur via a less-selective anion conductance.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…However, the plasma levels of ionized Ca 2+ do not significantly change in hens between 33 and 122 weeks of age. Thus, the decreased eggshell thickness may involve changes in shell gland function rather than availability of Ca 2+ for secretion [21]. A declining ability of the epithelium to transport Ca 2+ might be one of the major reasons for decreasing eggshell quality in older hens.…”
Section: Discussionmentioning
confidence: 99%
“…In this study we found that expression of all members of the SCNN1 gene family also increased significantly during eggshell formation in the uterus (Figure 2). The rates of Na + and anion transport are altered with age and in response to molting, which could potentially contribute to the decrease in shell thickness often associated with eggs from older birds [21]. These observations suggested a positive influence of Na + absorption on net Ca 2+ secretion [8].…”
Section: Discussionmentioning
confidence: 99%